ARTIKULASI TANGGUNG JAWAB , KEPEDULIAN LINGKUNGAN, DAN KERJA SAMA MELALUI PROGRAM SEKOLAH HIJAU DI LANDAK - Stela, Kristina Maya; Marzuki, Marzuki; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:The problem of this research is how is the articulation of responsibility, environmental care and cooperation through the elementary school green in the district of Landak. This study aims to improve the perception and articulation of responsibility, environmental care and cooperation through the elementary school green in the district of Landak. The research was conducted at 16 Kerohok public elementary schools and 42 state elementary school in Petai Bejambu. This study is a research that analyze the character of students. Data collection is done by using interviews, observation and documentation studies. The results of the study show that there is 1) very much is need of support from the education authorities, all schools, along with the community through groups of communities to create a harmony school with character. 2) creating environmental care for schools by involving all members of the school community and the community to maintain environmental cleanliness in order to create a comfortable atmosphere in the school environment both in the learning process and activities outside the classroom. 3) cooperation in creating mutual respect, self-harmony, harmony among others and harmony of the nature of all schools will support green school activities with a sense of belonging to a higher community facilitating the creation of green schools. Keywords :  Environmental awareness and collaboration through green     school programs responsibility.